Foxp3(+) regulatory T cell expansion required for sustaining pregnancy compromises host defense against prenatal bacterial pathogens - Rowe, Jared H. (2011)
Although pregnancy confers unique susceptibility to infection, the pregnancy-associated immune defects that erode host defense remain largely undefined. Herein, we demonstrate that expansion of immune-suppressive Foxp3(+) regulatory T cells (Tregs) which occurs physiologically during pregnancy or when experimentally induced in transgenic mice each caused enhanced susceptibility to prenatal pathogens including Listeria and Salmonella species. Reciprocally, infection susceptibility was uniformly reduced with Treg-ablation. Importantly however, the sustained expansion of maternal Tregs was essential for maintaining immune tolerance to the developing fetus because even partial transient ablation of Foxp3-expressing cells fractured maternal tolerance to fetal antigen and triggered fetal resorption. Interestingly, Foxp3 cell-intrinsic defects in the immune suppressive cytokine IL-10 alone were sufficient to override Treg-mediated infection susceptibility, while IL-10 was non-essential for sustaining pregnancy. Thus, maternal Treg expansion required for sustaining pregnancy creates naturally occurring holes in host defense that confers prenatal infection susceptibility.